1978
DOI: 10.1080/14640747808400671
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Subsidiary Tasks on Memory Retrieval from Long and Short Lists

Abstract: Burrows and Okada (1975) found that reaction time in an item recognition task was a monotonic but non-linear function of memory set size when set size varied from two to 20. A bilinear function with a steep slope for short lists and a shallow slope for long lists provided a good description of the data. Two experiments were conducted to determine whether the difference in slope between long and short lists arises from the extra attention devoted to, or rehearsal of, items within the span of immediate memory. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 23 publications
(14 reference statements)
3
29
2
Order By: Relevance
“…The RT functions for the alphabetic distance judgment showed basically the same pattern except that the steep linear portion was reduced to a magnitude of about 4. Although these results are highly counterintuitive in that memory quantification seems to operate in a serial fashion for small values, but in a parallel fashion for large values, they are consistent with Burrows and Okada (1975), Okada and Burrows (1978), and Baddeley and Ecob (1973) findings. Jou and Aldridge (1999) concluded that there is no memory subitizing, unlike in the perceptual domain.…”
Section: The Magic Number Four: Can It Explain Sternberg's Serial Memsupporting
confidence: 71%
See 1 more Smart Citation
“…The RT functions for the alphabetic distance judgment showed basically the same pattern except that the steep linear portion was reduced to a magnitude of about 4. Although these results are highly counterintuitive in that memory quantification seems to operate in a serial fashion for small values, but in a parallel fashion for large values, they are consistent with Burrows and Okada (1975), Okada and Burrows (1978), and Baddeley and Ecob (1973) findings. Jou and Aldridge (1999) concluded that there is no memory subitizing, unlike in the perceptual domain.…”
Section: The Magic Number Four: Can It Explain Sternberg's Serial Memsupporting
confidence: 71%
“…In these studies, the RT functions for MMS of 6 or smaller are typically characterized by steep linearity. But as the MMS exceeds 6, the functions become essentially flat (Baddeley & Ecob 1973;Burrows & Okada 1975;Okada & Burrows 1978) Those results were interpreted as suggesting that a serial access mode was in operation for small MSSs, but that a direct access mode is adopted when MSS exceeds 6. Jou (1998) used a fixed set version of the Sternberg task with MMSs varying from 1 to 20 and memory-set items randomly and repeatedly sampled from the 50 U.S. state names.…”
Section: The Magic Number Four: Can It Explain Sternberg's Serial Memmentioning
confidence: 98%
“…The dual false-memory retrieval process mirrors the dual process in veridical-memory retrieval from short and long lists in the Sternberg task (Burrows & Okada, 1975;Corballis et al, 1980;Okada & Burrows, 1978) and in other memory tasks (Jou & Aldridge, 1999). Thus, there seems to be a dual-process of retrieval associated with sub-and supramemory spans for false memory as well.…”
Section: Discussionmentioning
confidence: 71%
“…In a standard Sternberg paradigm, memory list length varies from 1 to 6 items, and the RT/MSS function obtained is linear. However, studies using MSSs beyond 6 indicated either a bilinear (Burrows & Okada, 1975;Okada & Burrows, 1978) or a logarithmic (Corballis, Katz, & Schwartz, 1980), rather than a linear, RT/MSS function. The bilinear RT functions showed a deflection point occurring at about MSS 7 separating an earlier steeper slope and a later shallower slope.…”
Section: Memory-span Limit and False Memorymentioning
confidence: 98%
“…There have been reports of absence of, or very weak, MSS effects (Diener, 1988(Diener, , 1990Stadler & Logan, 1989;Swanson, 1974), or linear, or logarithmic (bilinear, or quadratic, used interchangeably in this article) RT functions in Sternberg-type tasks across different studies or within the same studies depending on the materials or methods used. The suggested potential causes and the theoretical implications of these findings were numerous and varied and were lacking a consensus across the studies (Atkinson & Juola, 1973;Burrows & Okada, 1975;Corballis, Katz, & Schwartz, 1980;Juola, Taylor, & Young, 1974;Okada & Burrows, 1978;Simpson, 1972). The present study identified some methodological variables that reliably produced each of the above three types of MSS effects-that is, the linear, the null (or very weak), and the logarithmic (quadratic) RT functions.…”
mentioning
confidence: 71%